Penerapan hygiene dan sanitasi di restoran white canny - Gangga Daniswara Muku, I Dewa Gde; Widyatmaja, I Gusti Ngurah; Ariana, I Nyoman Jamin (Jurnal Kepariwisataan dan Hospitalitas, 2024)
This study aims to determine the application of hygiene and sanitation at the White Canny Restaurant Denpasar. The background of this research is that one of the most popular industries in the tourism sector is restaurants. Along with the development of the times, the restaurant has become one of the prima donna businesses that are always inherent in the tourism sector. This is the background and needs to be discussed in this paper because the application of hygiene and sanitation in a restaurant, especially in White Canny, really needs to be considered, this is based on some comments from consumers who come from guest comments. The purpose of this study was to determine the application of hygiene and sanitation at the White Canny Restaurant. The concept review used in this study is a review of the application, hygiene and sanitation, perceptions, consumers, and employees. The indicators used are face, nose, mouth, ears, finger and toe nails, physical fitness, work clothes, personal appearance, guest area, ceiling, walls, air ventilation, trash cans, hand washing and water hygiene, containers, moisture content, edible parts, separation, heat, clean tools, and handling. This study uses a questionnaire distributed online via google form to employees who work at White Canny and customers of White Canny. The sample in this study for employees amounted to 15 people and for customers amounted to 100 people. This type of research is quantitative analysis. The analysis uses a Likert scale. The results of this study, among others, based on the table of tabulation data on the questionnaire data, the average score of the employee's answers regarding three variables such as personal hygiene, restaurant area environment, and food and beverage hygiene was 4.47 with the category strongly agree. This shows that the employees have actually implemented the application of hygiene and sanitation at the White Canny restaurant. Based on the table of results tabulation of questionnaire data, the average score of consumer answers regarding three variables such as personal hygiene, restaurant area environment, and food and beverage hygiene is 4.26 with the category strongly agree. This shows that consumers respond strongly to the application of hygiene and sanitation in the White Canny restaurant. Key Word : Application of Hygiene and Sanitation, employees, customers.